OXYGEN TRANSFER IN A THREE-PHASE FLUIDISED BED BIOREACTOR WITH NOVEL BIOMASS SUPPORT WHEN USED IN INDUSTRIAL WASTEWATER TREATMENT - Manyele, S. V.; Halfani, M. R.; Sokol, W. (Tanzania Journal of Engineering and Technology, 2018)
Abstract